2013
DOI: 10.1111/zph.12051
|View full text |Cite
|
Sign up to set email alerts
|

Potential Animal and Environmental Sources of Q Fever Infection for Humans in Queensland

Abstract: Q fever is a vaccine-preventable disease; despite this, high annual notification numbers are still recorded in Australia. We have previously shown seroprevalence in Queensland metropolitan regions is approaching that of rural areas. This study investigated the presence of nucleic acid from Coxiella burnetii, the agent responsible for Q fever, in a number of animal and environmental samples collected throughout Queensland, to identify potential sources of human infection. Samples were collected from 129 geograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
75
2
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(84 citation statements)
references
References 46 publications
(57 reference statements)
4
75
2
3
Order By: Relevance
“…However, present research and some other previous reports showed that there was no correlation between seropositive cases and direct contact with farm animals (Gale et al, 2007;Tozer et al, 2014). It was hypothesised that other risk factors (except farm animals contact) like wildlife contact, tick exposure or pet-owners who worked closely with other farm animals would have a positive association with seropositivity to C. burnetii in the pets (Cooper et al, 2011).…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…However, present research and some other previous reports showed that there was no correlation between seropositive cases and direct contact with farm animals (Gale et al, 2007;Tozer et al, 2014). It was hypothesised that other risk factors (except farm animals contact) like wildlife contact, tick exposure or pet-owners who worked closely with other farm animals would have a positive association with seropositivity to C. burnetii in the pets (Cooper et al, 2011).…”
Section: Discussioncontrasting
confidence: 46%
“…In present study, breed, type of housing, type of food and presence of clinical signs showed no significant differences between positive and negative cases. Based on the literature, high prevalence of C. burnetii has been reported in the urine of dogs and human infection has been directly linked to the pet dogs (Komiya et al, 2003;Tozer et al, 2014). Therefore, no clinical signs of positive cases might have a decisive role in human infections.…”
Section: Discussionmentioning
confidence: 99%
“…Although the majority of human Q fever outbreaks are linked to the transmission of C. burnetii from domestic ruminants (4,5), the ability of C. burnetii to infect wild hosts (3,6) and its high environmental resistance (1) make wildlife species potential reservoirs of C. burnetii. Based on this hypothesis, wildlife could maintain C. burnetii and transmit it to wildlife (7), domestic animals (8), or humans (9). It is therefore of paramount relevance (i) to identify those potential wild reservoir species that could, through direct and indirect interactions, transmit C. burnetii to target species (domestic animals and humans) and (ii) to determine which environmental factors are the main drivers of C. burnetii within the most relevant wild reservoirs.…”
mentioning
confidence: 99%
“…In Canada, a dog-related outbreak of Q fever was reported [135]. Although arthropod-borne transmission of Q fever in humans is not considered to be significant, C. burnetii has been isolated from ticks collected from dogs [136], and as ticks shed high loads of bacteria in their feces and saliva, they may be another potential source of bacterial transmission.…”
Section: One Healthmentioning
confidence: 99%